THE RELATIONSHIP BETWEEN FORM AND CONTENT IN THE TRANSLATION OF ALEKSANDR FEINBERG’S POEMS. (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta'limning o'rni hamda rivojlanish omillari, 2025)
Abstract: Translating Feinberg’s poetry into English involves not only conveying the linguistic peculiarities but also preserving the balance between form and content, making it a complex cognitive process.This article discusses the main challenges encountered in the process of translating Feinberg’s poems and possible ways to address them.